PELAKSANAAN MODEL PEMBELAJARAN TEMATIK BAGI SISWA TUNAGRAHITA RINGAN DI SLB HIKMAH REFORMASI PADANG - Irwandi - Irwandi (Universitas Negeri Padang, 2012)
The background of this research due to the difficulties experienced by classroom teachers in the implementation of thematic learning for students in special schools mild mental retardation field Wisdom reform. Unexplained difficulty is evident from the teacher presents the material in a less integrated, the use of learning methods that monotony and lack of media used to support the teacher .. This study used a qualitative descriptive method. The results of the implementation of the thematic learning begins with the learning program preparing them to prepare a syllabus and lesson plan implementation, attention kasiapan students or teachers. Initial activities starting from prayer, attendance, conditioned students, and appersepsi. Presentation materials used by the teacher was explaining the lesson separately so less visible alignment. The method used in other anatar learning lectures, discussion, drill and assignments. Activities end or cover done by concluding lesson with students and provide training. Constraints faced by teachers in preparing teaching materials that teachers are lacking thematic knowing about linking material on each subject, combined, teachers rarely use the media in the implementation of learning.